Curriculum Management for Strengthening Religious Moderation in Islamic Boarding Schools Al Mukmin - Doki Hermanto (PT. Islamic Research Publisher, 2023)
PPIM Al-Mukmin Ngruki has long been associated with public controversy, particularly since its early resistance to the New Order government’s policy of adopting Pancasila as the sole state ideology. The involvement of several founders, including Abu Bakar Ba’asyir and Abdullah Sungkar, in political opposition further shaped the institution’s contested image. In addition, the association of some alumni with acts of terrorism has contributed to persistent stigmatization, often leading to generalized assumptions about the pesantren and its broader community. This study aims to critically examine the cultivation and implementation of tolerance values within PPIM Ngruki, particularly in the context of religious moderation education. This research employs a qualitative approach through a literature study method. Data were collected from relevant academic publications, policy reports, and prior empirical studies addressing pesantren education, radicalism, and religious moderation. The data were analyzed using content analysis to identify patterns related to curriculum design, pedagogical practices, and institutional orientations toward tolerance. The findings indicate that PPIM Ngruki has systematically integrated tolerance values into its educational framework. This is reflected in curriculum content, teacher roles, and student engagement, all of which support the strengthening of religious moderation. Two key indicators highlight this orientation: first, the institution does not enforce the formal implementation of Islamic law as a rigid political agenda; second, it demonstrates a moderate and adaptive stance toward socio-political dynamics. These findings challenge prevailing stereotypes by showing a more nuanced institutional reality. This study contributes to the academic discourse by providing a balanced and evidence-based perspective on pesantren often labeled as conservative, emphasizing the importance of contextual analysis in understanding religious education and moderation in Indonesia.